Marketing a tourism industry in late stage decline: The case of the Isle of Man - Brendan Canavan; Len Tiu Wright (Cogent Business & Management, 2015)
Qualitative interviews in the Isle of Man uncovered local perceptions of a tourism industry in late stage decline. Social impacts of decline are pronounced including facilities loss, cultural changes and a heightening of perceived peripherality: which taken together undermine local identity. Tourists are welcomed as they help to affirm the pride residents have in their island in creating a more active atmosphere, to provide social interaction opportunities and to combat negative stereotyping. Thus, findings emphasise the diverse, unique and persistent benefits of tourism in the Isle of Man, despite its decline. Destination marketing recommendations are therefore made to better address the experiences and desires of communities experiencing decline.
Keywords: 650